(untitled) (Torani Journal of Fisheries and Marine Science, 2017)
This study was conducted to examine the effect of the traditional conservation system "Tiyaitiki" toward populations and diversity of rabbit fish (family Siganidae) in Tablasupa Coastal Area, Jayapura Regency. By hypothesis Tiyaitiki system is very effective in enhancing the functioning of ecosystems, populations, and species diversity of rabbitfish. Using the method of VES and transect lines, spacious observation area is 81,000 m2. The data were analyzed using diversity index Shannon-Wiener (H ’), Index Evenness (E), Index dominance Simpson (D) and Population Density (PD). The result showed Tablasupa Coastal area has 10 rabbit fish species and 873 individuals. The level of diversity is categorized as moderate or 1.7 and the population is more likely to be uniform, as well as population density tend to be moderate. The increasing number of rabbitfish species and populations affected by the increase of live coral cover and increased density of seagrass by the system Tiyaitiki in Tablasupa Coast. Tiyaitiki traditional conservation system capable of triggering an increase in the ecological function of seagrass and coral reefs, which significantly affected the growth of population and the diversity of fish species in the waters Rabbitfish family Siganidae in Tablasupa Coastal area. Keywords: Rabbit fish, Tablasupa, Tiyaitiki, Jayapura